2020
DOI: 10.1021/acsabm.0c00795
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Block Polypeptide Composed of d-Type Amino Acids: A Therapeutics Delivery Platform to Inhibit Biofilm Formation of Drug-Resistant Bacteria

Abstract: Antibiotic resistance of bacteria has been widely developed due to biofilm protection and separating the bacteria from antibiotics. The phenomenon of biofilm inhibition or disassembly by D-amino acids (DAAs) has been reported recently, while it was also challenged by some other scientists. Presuming DAAs work for biofilms on the surface of bacteria, delivery of the DAAs to disease sites is important while small DAAs are easily removed by kidney. To resolve the above issues, it is urgent to develop a biofilm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Chen and co-workers 92 demonstrated the biofilm disassembly and inhibition ability of cationic D-type polypeptides, as D-type amino acids (DAAs) were found to prevent existing biofilm, 93,94 though it is questioned by many scientists. The amphiphilic polypeptide, poly(L-lysine) 33 -block-poly(D-phenylalanine) 14 was synthesized by N-carboxyanhydride (NCA) ringopening polymerization using hexamethyldisilazane (HMDS) as an initiator.…”
Section: Cationic and Charge-switchable Polymersmentioning
confidence: 99%
“…Chen and co-workers 92 demonstrated the biofilm disassembly and inhibition ability of cationic D-type polypeptides, as D-type amino acids (DAAs) were found to prevent existing biofilm, 93,94 though it is questioned by many scientists. The amphiphilic polypeptide, poly(L-lysine) 33 -block-poly(D-phenylalanine) 14 was synthesized by N-carboxyanhydride (NCA) ringopening polymerization using hexamethyldisilazane (HMDS) as an initiator.…”
Section: Cationic and Charge-switchable Polymersmentioning
confidence: 99%
“…synthesized a poly(CBZ‐l‐lysine) 33 ‐block‐poly(d‐phenylalanine) 14 d‐type polypeptide via an N ‐carboxyanhydride ring‐opening polymerization reaction, which can self‐assemble into nanocapsules for penicillin G delivery. [ 129 ] Gingerol is the main component of ginger, which reduces biofilm formation by interfering with the interaction between an extracellular diffusible N ‐(3‐oxododecanoyl)‐ l ‐homoserine lactone (OdDHL) and its cognate receptor LasR in P. aeruginosa . [ 124 ] In Byun's further study, the impacts of the different parts of (S)‐6‐gingerol were demonstrated (Figure 8D).…”
Section: Disrupting Biofilm Integrity To Heighten the Biofilm Penetra...mentioning
confidence: 99%
“…Using Dispersin B, a biofilm-dispersing enzyme, in combination with peptides, eradicated ∼70% of S. epidermidis biofilms compared to only ∼35% by Dispersin B alone ( Chen and Lee, 2018 ). Further, D-amino acids from B. subtilis , known to signal for biofilm disassembly, were found to inhibit the development of S. aureus biofilms ( Chen et al, 2020 ). Intriguingly, honey – a natural product, has also shown anti-biofilm effects by inhibiting P. aeruginosa biofilm formation and reducing its established biofilms ( Lu et al, 2019 ).…”
Section: Innovative Treatment Strategies For Controlling Biofilmsmentioning
confidence: 99%